Mimar Sinan Narrated by Tezkiretü'l-Bünyan and Tezkiretü'l-Ebniye A Critique on the Book Mimar Sinan Memories - Leila Ghaffari; Jamal Arabzadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The cultural identity of a society is influenced by many factors, including religion, customs, art, and especially architecture. Moreover, the practical aspect of architecture in human life has made it important in the formation of civilizations such as Islam. The objective appearance of this civilization in the form of valuable artistic structures is due to the knowledge and skill of prominent architects like Sinan. Therefore, to get acquainted with architects and their unique perspectives, studying of remain historical cited texts is considerable. Due to Sinan's special place in the development of Ottoman architecture, as well as Islamic architecture, exploring the texts related to him, especially what was said by Sinan, is fruitful. Regarding this article, the Persian translation of his two valuable treatises in the form of the book "Tezkiretü'l-Bünyan and Tezkiretü'l-Ebniye: Mimar Sinan Memories" has been reviewed. So, after presenting formic characteristics of the book, historical aspects of pre-modern architecture and architects of Islamic world, the life and works of Sinan, his Biography, his treatise’s introduction and finally a comparison between them and a similar text, Risale-yi Mimariye are discussed; Hence this comparison will be effective in better understanding the thoughts of the architects of that time, especially Sinan.